Analysis of Water Quality Status in Porong River, Sidoarjo by Using NSF-WQI Index (Nasional Sanitation Foundation – Water Quality Index) - Muhammad Triaji; Yenny Risjani; Mohammad Mahmudi (Indonesian Journal of Environment and Sustainable Development, 2017)
Porong River can be described as a walking landfill that can deliver variety of waste to go to estuary, where it would be settled and accumulated. That numerous waste in the river will lead to pollution and provide huge negative impact for water quality status and organism life. Therefore, this study aim to assess the extent of contamination that occurred in Porong river by using WQI NSF (National Sanitation Foundation - Water Quality Index) Index. The research site was in along Porong river from Mojokerto to Jaban Sidoarjo estuary, which will be divided into 7 sampling sites. Next, the determination of the sampling location was conducted by using purposive sampling method. The use of WQI NSF index is able to analyze data using 8 or 9 parameters. In order to obtain complete overview of water quality status in Porong River, then this research used 9 parameters, including: BOD, DO, nitrate, total phosphate, temperature, turbidity, total solids, pH, and  Fecal Coliform. Based on the results of 9 parameters data analysis using NSF-WQI index, it is known that the recent water quality status in Porong River is classified as Medium criteria. By knowing the results of data analysis showing the criteria of medium, so we are obliged to maintain the water cleanness, so that the water quality status will not decline.Keywords: NSF-WQI, Porong River, Status of Water Quality